Cloud-based secure healthcare framework by using enhanced ciphertext policy attribute-based encryption scheme - Mohd Satar, Siti Dhalila; Mohamed, Mohamad Afendee; Hussin, Masnida; Mohd Hanapi, Zurina (SAI Organization, 2021)
Cloud computing is an emerging technology that has been used to provide better healthcare services to the users because of its convenient and economical features. Noted that the healthcare services required fast and reliable data sharing at anytime from anywhere for better monitoring and decision making in medical requirements. However, the privacy and integrity of electronic healthcare record become a significant issue during data sharing and outsourcing in Cloud. The data privacy of clients/patients is important in healthcare services where exposure of the data to unauthorized parties is unexceptional. In order to address this security loophole, this paper presents a Cloud-based Secure Healthcare Framework (SecHS) to offer safe access to healthcare and medical data. Specifically, this paper enhance the Ciphertext Policy Attribute-Based Encryption (CP-ABE) scheme by adding two more modules which aims to provide fine-grained access control and offer privacy and integrity of data. It facilitates encryption and hashing schemes. The proposed framework is compared with existing frameworks that used CP-ABE scheme. It shows the SecHS offers better features towards securing the healthcare services data. Optimistically, data security requirements such as privacy, integrity and fine-grained access control are required to effectively proposed for assuring data sharing in the Cloud environment.